Odpowiedzi

2009-12-31T13:21:56+01:00
4(2x+3)-2(4y-1)=30
5x+1 /3 - y-3 /4 = 3

8x+12-8y+2=30
20x+4 /12 - 3y-9 /12 = 3

8x-8y=16
20x+4-3y+9=36

x-y=2
20x-3y=23

-3x+3y=-6
20x-3y=23

17x= 17
x=1
1-y=2
y=-1

x=1
y=-1
  • Użytkownik Zadane
2009-12-31T13:26:17+01:00
4(2x+3)-2(4y-1)=30
(5x+1)/3-(y-3)/4=3

8x+12-8y+2=30
(20x+4)/12-(3y-9)/12=3 /×12

8x-8y=30-14 /÷8
20x+4-3y+9=36

x-y=2
20x-3y=23

x=2+y
20(2+y)-3y=23

40+20y-3y=23
17y = -17 /÷17
y= -1

x-y=2
x-(-1)=2
x+1=2 /-1
x=1

x=1
y=-1
2009-12-31T13:29:27+01:00
4(2x+3)-2(4y-1)=30
5x+⅓ -y-¾=3

8x+12-8y+2=30
5x-y= 3+¾-⅓

8x-8y=30-2-12
5x-y= 3+ 9/12 - 4/12

8x-8y= 16
5x-y=3 +5/12

8x-8y=16
5x-y=41/12 /*12

8x-8y=16 /*(-3)
60x-12y=41 /*2

-24x+24y=-48
120x-24y=82

96x=34 /:96
x=34/96

170/96 - y= 41/12
-y= 41/12 - 170/96
-y= -33/96- 170/96
-y= -203/96
y=203/96

x=34/96
y=2 11/96